Imatinib preserves blood–brain barrier integrity following experimental subarachnoid hemorrhage in rats. Issue 1 (4th September 2014) - Zhan, Yan; Krafft, Paul R.; Lekic, Tim; Ma, Qingyi; Souvenir, Rhonda; Zhang, John H.; Tang, Jiping
<x xml:space="preserve">Abstract</x> Blood–brain barrier (BBB) disruption and consequent edema formation contribute to the development of early brain injury following subarachnoid hemorrhage (SAH). Various cerebrovascular insults result in increased platelet‐derived growth factor receptor (PDGFR)‐α stimulation, which has been linked to BBB breakdown and edema formation. This study examines whether imatinib, a PDGFR inhibitor, can preserve BBB integrity in a rat endovascular perforation SAH model. Imatinib (40 or 120 mg/kg) or a vehicle was administered intraperitoneally at 1 hr after SAH induction. BBB leakage, brain edema, and neurological deficits were evaluated. Total and phosphorylated protein expressions of PDGFR‐α, c‐Src, c‐Jun N‐terminal kinase (JNK), and c‐Jun were measured, and enzymatic activities of matrix metalloproteinase (MMP)−2 and MMP‐9 were determined in the injured brain. Imatinib treatment significantly ameliorated BBB leakage and edema formation 24 hr after SAH, which was paralleled by improved neurological functions. Decreased brain expressions of phosphorylated PDGFR‐α, c‐Src, JNK, and c‐Jun as well as reduced MMP‐9 activities were found in treated animals. PDGFR‐α inhibition preserved BBB integrity following experimental SAH; however, the protective mechanisms remain to be elucidated. Targeting PDGFR‐α signaling might be advantageous to ameliorate early brain injury following SAH. © 2014 Wiley Periodicals, Inc.